Alcohol prevention at sporting events: study protocol for a quasi-experimental control group study. (December 2016) - Durbeej, Natalie; Elgán, Tobias; Jalling, Camilla; Gripenberg, Johanna
Abstract Background Alcohol intoxication and overserving of alcohol at sporting events are of great concern, given the relationships between alcohol consumption, public disturbances, and violence. During recent years this matter has been on the agenda for Swedish policymakers, authorities and key stakeholders, with demands that actions be taken. There is promising potential for utilizing an environmental approach to alcohol prevention as a strategy to reduce the level of alcohol intoxication among spectators at sporting events. Examples of prevention strategies may be community mobilization, Responsible Beverage Service training, policy work, and improved controls and sanctions. This paper describes the design of a quasi-experimental control group study to examine the effects of a multi-component community-based alcohol intervention at matches in the Swedish Premier Football League. Methods A baseline assessment was conducted during 2015 and at least two follow-up assessments will be conducted in 2016 and 2017. The two largest cities in Sweden are included in the study, with Stockholm as the intervention area and Gothenburg as the control area. The setting is Licensed Premises (LP) inside and outside Swedish football arenas, in addition to arena entrances. Spectators are randomly selected and invited to participate in the study by providing a breath alcohol sample as a proxy for Blood Alcohol Concentration (BAC). Actors are hired and trained by an expert panel to act out a standardized scene of severe pseudo-intoxication. Four types of cross-sectional data are generated: (i) BAC levels among ≥ 4 200 spectators, frequency of alcohol service to pseudo-intoxicated patrons attempting to purchase alcohol at LP (ii) outside the arenas (≥200 attempts) and (iii) inside the arenas (≥ 200 attempts), and (iv) frequency of security staff interventions towards pseudo-intoxicated patrons attempting to enter the arenas (≥ 200 attempts). Discussion There is an urgent need nationally and internationally to reduce alcohol-related problems at sporting events, and it is essential to test prevention strategies to reduce intoxication levels among spectators. This project makes an important contribution not only to the research community, but also to enabling public health officials, decision-makers, authorities, the general public, and the sports community, to implement appropriate evidence-based strategies.